2011
DOI: 10.1063/1.3532543
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and phase transitions in a silica clathrate

Abstract: Melanophlogite, a low-pressure silica polymorph, has been extensively studied at different temperatures and pressures by molecular dynamics simulations. While the high-temperature form is confirmed as cubic, the low-temperature phase is found to be slightly distorted, in agreement with experiments. With increasing pressure, the crystalline character is gradually lost. At 8 GPa, the radial distribution function is consistent with an amorphous state. Like pristine glass, the topology changes, plastic behavior, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…38 This potential has shown to capture the correct phases for SiO 2 and reproduce most of the observed anomalies of the silica. 21,[38][39][40][41][42] The simulation started from 46 SiO 2 molecules clathrate framework with a time step ∼0.72 fs (30 a.u.) in NPT ensemble at range −10 to 10 GPa of pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 This potential has shown to capture the correct phases for SiO 2 and reproduce most of the observed anomalies of the silica. 21,[38][39][40][41][42] The simulation started from 46 SiO 2 molecules clathrate framework with a time step ∼0.72 fs (30 a.u.) in NPT ensemble at range −10 to 10 GPa of pressure.…”
Section: Methodsmentioning
confidence: 99%
“…17 It shows slightly distorted structure with a lower symmetry when the temperature is decreased. 18,21 The existence of melanophlogite encourages the possibility to have similar clathrate structures of CO 2 and GeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15]31 Zwijnenburg et al 32 have compared experimental thermochemical data for silica polymorphs with simulation studies using different force fields and with DFT calculations. More recently, Liang and coworkers 33 have reported molecular dynamics studies of the structural transitions and phase transformations in melanophlogite, a low-pressure silica polymorph.…”
Section: Introductionmentioning
confidence: 99%
“…Melanophlogite containing CO 2 , N 2 and CH 4 is tetragonal (Nakagawa et al, 2001). If only CH 4 is present, the symmetry is cubic (Tribaudino et al, 2008), whereas guest-free melanophlogite has been predicted to have an orthorhombic structure by molecular-dynamics simulations (Liang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In guest-free melanophlogite, almost complete amorphization was found at P >3 GPa (Xu et al 2007), whereas diffraction peaks up to 24 GPa were reported for a melanophlogite containing extra-framework guest molecules (Tribaudino et al, 2008;Yagi et al, 2007). Recently, it has been predicted by molecular-dynamics calculations, that amorphization would begin in guest-free melanophlogite at P = 8 GPa, whereas it would occur at a higher pressure in guest-bearing forms (Liang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%